(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Buddhaas the transcendental, eternal and absolute, who saves all living beingsthrough his triple body, dharma,sambhoga etc. Maheyenists believe in an infinitenumber of Bodhisattvas, whotake vow to attain Buddha-hood and to liberate all beings. Maheyenists emphasize both the lifeof monk and that of householder. They consider wisdom, devotion as the means toliberation. Maheyenists regard Nirvana as transcendental experienceof sunyata and is a positivestate. Yoga believe in onlymind, which constructs the conditioned world. According to them, Alayavijana is real and all objects, which are manifested from Alayavijana, are unreal. Madhya-mikas believe in sunyata or emptiness which is theessence behind the impermanent phenomena and all things are the manifestationof sunyata. Enlightenment,according to Mahayana, does notmean simply the understanding of the Four Noble Truths in their positive statesbut the experience of sunyata orBuddha-nature that constitutes the original enlightenment of all creatures. Andthe Buddha is not merely the Enlightened One in the old sense but anomniscient. This is why the Buddha’s enlightenment is higher than that of Arhats.